2018
DOI: 10.1103/physrevb.97.014508
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the vortex line density in superfluid counterflow turbulence

Abstract: Describing superfluid turbulence at intermediate scales between the inter-vortex distance and the macroscale requires an acceptable equation of motion for the density of quantized vortex lines L. The closure of such an equation for superfluid inhomogeneous flows requires additional inputs besides L and the normal and superfluid velocity fields. In this paper we offer a minimal closure using one additional anisotropy parameter I l0 . Using the example of counterflow superfluid turbulence we derive two coupled c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, as the line scans displayed in 9(c) show, the contrast appears to have reversed after increasing the temperature to 4.5K. This would be a very interesting result but care needs to be taken, for instance the shift of ~1.75µm may have occurred due to thermal expansion; more evidence of this is needed [12] .…”
Section: Tikrit Journal Of Pure Science 23 (8) 2018 Issn: 1813 -1662 ...mentioning
confidence: 91%
“…However, as the line scans displayed in 9(c) show, the contrast appears to have reversed after increasing the temperature to 4.5K. This would be a very interesting result but care needs to be taken, for instance the shift of ~1.75µm may have occurred due to thermal expansion; more evidence of this is needed [12] .…”
Section: Tikrit Journal Of Pure Science 23 (8) 2018 Issn: 1813 -1662 ...mentioning
confidence: 91%
“…Most of attempts to find equation of motion for the vortex line density so far dealt with steady-state tangles and represented P 1 and D in Eq. ( 10) as functions of L and V ns only for the homogeneous tangles, adding the curvature, the binormal, and their derivatives [17][18][19] in the inhomogeneous case. In the current situation of the inhomogeneous and growing tangle we can not expect a unique closure.…”
Section: Properties Of F (L)mentioning
confidence: 99%
“…Recent advances in the experimental techniques, including flow visualization [22][23][24] , as well as increasing computing power, renewed the interest to the spatial inhomogeneity due to presence of channel walls 19,[25][26][27][28][29][30][31] and spatially-resolved investigations of the transient behavior in the thermal counterflow 32 . The latter work showed that the vortex tangle that eventually fills the whole channel, grows starting from a number of remnant vortex rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation